2018
DOI: 10.25226/bboc.v138i2.2018.a3
|View full text |Cite
|
Sign up to set email alerts
|

The ambiguous identity of Turdus mustelinus Wilson, and a neotype designation for the Veery Catharus fuscescens (Stephens)

Abstract: The long-recognised name of the Veery Catharus fuscescens (Stephens 1817) was intended to replace Tawny Thrush Turdus mustelinus Wilson, 1812, which was preoccupied by T. mustelinus J. F. Gmelin, 1789. Herein, I demonstrate that T. mustelinus Wilson is unidentifiable because it was based on attributes shared by more than one species, including some features that are a better match to other Catharus species than to Veery. None of the specimens mentioned in Wilson's description is extant. To maintain traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…If anything, they cast more doubt on Nuttall's understanding of the species in question: 'At intervals, on the commencement of the breeding period, we heard their notes, bearing indeed, some resemblance to the quaint warble of the Veery or Wilson's Thrush [i.e. Wilson's composite T. mustelinus, see Halley 2018], though quite distinct, and easily recognizable from the notes of that Atlantic species. Its song was also more brief and interrupted, and the bird more shy and difficult of access.…”
Section: Behavioural Observations and Nest Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…If anything, they cast more doubt on Nuttall's understanding of the species in question: 'At intervals, on the commencement of the breeding period, we heard their notes, bearing indeed, some resemblance to the quaint warble of the Veery or Wilson's Thrush [i.e. Wilson's composite T. mustelinus, see Halley 2018], though quite distinct, and easily recognizable from the notes of that Atlantic species. Its song was also more brief and interrupted, and the bird more shy and difficult of access.…”
Section: Behavioural Observations and Nest Descriptionmentioning
confidence: 99%
“…The convoluted nomenclature of the nightingale-thrushes (Aves: Turdidae: Catharus) began with a taxonomically composite species (Turdus minor J. F. Gmelin, 1789) that was a source of widespread confusion until the mid-19th century. In a recent paper, I reviewed the early history of T. minor and demonstrated that Alexander Wilson (1766Wilson ( -1813, who split the composite T. minor into two species that were also composites (T. solitarius and T. mustelinus; Wilson, 1812), did not correctly distinguish any of the five species now recognised as breeders in eastern North America (Halley 2018). Those species are: Hermit Thrush Catharus guttatus (Pallas, 1811), Veery C. fuscescens (Stephens, 1817; for neotypification see Halley 2018), Swainson's Thrush C. ustulatus (Nuttall, 1840), Greycheeked Thrush C. minimus (Lafresnaye, 1848) and Bicknell's Thrush C. bicknelli (Ridgway, 1882).…”
mentioning
confidence: 99%
See 3 more Smart Citations